(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes the economic, legal, and methodological foundations of the business entity stability rating system developed under Uzbekistan’s regulatory framework. The rating indicators are reviewed in comparison with international practices and evaluated in the context of digital fiscal governance and tax discipline. Practical challenges in the system are identified, and improvement recommendations are proposed. The study provides theoretical insights and policy suggestions aimed at enhancing the effectiveness of fiscal reforms in Uzbekistan.